NEOLITHIC/NEO-ENEOLITHIC GEOMETRIC MICROLITHS OF RAKUSHECHNY YAR SITE - Uspenskaa, Olesa Igorevna; Dolbunova, Ekaterina Vladimirovna; Gorodeckaa, Susanna Pavlovna; Larionova, Alisa Valer'evna; Mazurkevic, Andrej Nikolaevic (History, Archeology and Ethnography of the Caucasus, 2024)
Geometric microliths were found at various Mesolithic-Neolithic sites of the Pontic-Caspian region. The research of Rakushechny Yar settlement allowed us to reveal stable series of geometrical microliths originating from the excavations I and II of T.D.Belanovskaya and obtained in the course of recent research. The production technology of geometric microliths has a number of common features in raw material selection, determined by the limited availability of material, blanks, and secondary processing. New excavations and recording techniques allowed us to attribute individual types with chronological micro-horizons within Early Neolithic (ca. 5720-5620 and 5670-5520 BC), the final stage of the Early Neolithic (ca. 5620-5520/5410-5310 BC) and the Late Neolithic-Eneolithic (ca. 5474-5046/5010-4549 BC). The percentage content of microliths in the toolkit is about 4-6% for various layers of Rakushechny Yar site. As a result of the new excavations, the number of geometric microliths was increased, which is largely due to the excavation methodology. It is possible to assume a significant increase in their number with the expansion of the investigated area, with the same ratio of microlithes in the total flint industry of the site. The article discusses the area of distribution of geometric microliths. Geometric microliths with backed sides are located in the western part of the Pontic-Caspian region. Simple trapezoids, a widespread type of geometric microliths for the Neolithic, often coexisted with trapezoids with a retouched dorsal surface in this region, or preceded them. The latter type was widespread in the vast territory of the Pontic-Caspian region.
Keywords: geometrical microliths; trapezoids with backed side; trapezoids with a retouched dorsal surface; Neolithic; Neo-Eneolithic; Ponto-Caspian region; macro-traces